KETERLIBATAN ORANG TUA DALAM PEMBELAJARAN DARING ANAK PAUD DAN MADRASAH SELAMA MASA PANDEMIC COVID-19 - Andini Eva Saputri; Khaeruman; Arta Rusidarma Putra; Dea Aprilianti Syam; Syahril Kirom; Rensi Passasung (Bajang Institute, 2021)
The increasing Covid-19 virus in Indonesia has made the central and regional governments issue various appeals, regulations, and policies that have been given to people throughout Indonesia, including Padasuka Village, Baros District, Serang Regency. The specific objectives are 1) Increase understanding of parental involvement in the learning process for PAUD and Madrasah children; 2) implement ways that can be done during the pandemic period. Parents can be involved not only at home, but their involvement in school is also very necessary and recommended, at least to monitor and monitor the activities and behavior of their children so that unwanted things do not happen such as bullying, discrimination, child and juvenile delinquency. and others. Facilities that can be used as online learning media that will be applied to teachers and students include e-learning, zoom meeting applications, and WhatsApp social media. These facilities can be used optimally, as a medium in carrying out learning such as in the classroom for teachers and students in Padasuka Village, Baros District, Serang Regency